Diet and activity budget of Rhinopithecus roxellana in the Qinling Mountains, China - Guo, Songtao; Li, Baoguo; Watanabe, Kunio (Primates, 2007)
We collected data on diet and daytime activity budget, and investigated the phenology of food trees and food abundance for a group of Rhinopithecus roxellana on the East Ridge of Yuhuangmiao in the Qinling Mountains from November 2001 to December 2003. We calculated the seasonal activity budget using data collected by scan sampling from 84 full-day observations (winter 16, spring 18, summer 28, autumn 22 days). During scan sampling we recorded behavioral states, and the food items and species consumed. The subjects consumed 84 plant species, including trees and shrubs of 29 families, and lichens. Food species varied seasonally. The overall diet of R. roxellana consisted of 29.4% fruit/seeds, 29.0% lichens, 24.0% leaves, 11.1% bark, 4.2% buds, 1.3% twigs and 1.0% unidentified items. Because the abundance of different food items varied seasonally, the monkeys had to shift their major food items seasonally. The annual activity budget of R. roxellana was 36.2% time spent resting, 35.8% feeding, 22.9% moving, and 5.1% other behavior. Seasonal changes in activity budget were observed. R. roxellana spent more time moving in autumn, when the quality of the food might be highest, and least time moving in winter when the food quality might be lowest. Thus, this type of monkey has a passive foraging strategy.